Designing a Quality Model for justifying the Authenticity of Qualitative Research: Validation and Verification of References - Habib, Basit; Mahmood, Shahzad; Khakwani, Sohail Khan (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The Research in social science has a vital impact on the historical background of different event. These events are to be studied under the umbrella of qualitative research methodology. This methodology is based on the critical overview of any event or set of events related to a certain problem statement. To evaluate the authenticity of such research which is conducted on the bases of oral history, it is necessary to define a certain tool which is in hierarchy order and if qualitative research is to be conducted should be gone through using the certain tool. In this paper such a quality model is generated from various aspect of computational quality model which can be helpful for the social scientist to see the authenticity of the references and methodology used during the research of oral history.